Implementation of School Management Functions in Effort to Improve the Quality of Education - Irsyadiah, Nur (Budapest International Research and Critics University, 2021)
Management education is the whole process of cooperation by utilizing all personnel and material resources available and appropriate to achieve educational goals that have been set effectively and efficiently. Or as a series of activities or the overall control process a number of cooperative efforts to achieve the goal of education is systematically organized in certain environments, especially in the form of formal educational institutions. Management education in schools is a concept that offers autonomy to determine madrasah madrassa policy in order to improve the quality of education and learning that are at the school. Functions-school education management functions include; planning, organizing and monitoring implementation. To realize the improvement of the quality of education and learning in senior high school As-Syafi'iyah 01 Jakarta those with the implementation of the management functions are affective and efficient education. This study aims to investigate the implementation of management functions to improve the quality of senior high school, knowing the steps and strategies for the management in senior high school, and determine the factors supporting and hindering the implementation of management functions in senior high school As-Syafi'iyah. The results of this study demonstrate that the performance of the functions of school management in improving the quality of education in senior high school As-Syafi'iyah 01 Jakarta has been running optimally.